Successfully Reducing Sitting Time Can Improve Metabolic Flexibility - Garthwaite, Taru; Sjöros, Tanja; Laine, Saara; Koivumäki, Mikko; Vähä‐Ypyä, Henri; Norha, Jooa; Kallio, Petri; Saarenhovi, Maria; Löyttyniemi, Eliisa; Sievänen, Harri; Houttu, Noora; Laitinen, Kirsi; et al. (John Wiley & Sons, 2026)
Impaired metabolic flexibility (MetFlex; the ability to regulate substrate oxidation) and sedentary behavior are both linked to cardiometabolic diseases, but the relationship between the two is not fully elucidated. This study investigated the effects of reduced sedentary time on MetFlex. Sixty-four sedentary adults with metabolic syndrome were randomized into intervention (INT, n = 33) and control (CON, n = 31) groups. INT aimed to reduce sedentary time by 1 h/day by increasing standing and non-exercise physical activity (PA) for 6 months, with continuous accelerometry. Substrate oxidation and MetFlex [ΔRER (respiratory exchange ratio)] from fasting to hyperinsulinemic-euglycemic clamp and low- to maximal-intensity exercise were assessed with indirect calorimetry. Intervention effects between INT and CON were analyzed with mixed models, and secondary analyses examined the effects based on accelerometer-derived behavior changes. INT reduced sedentary time by 41 min/day. Neither insulin- nor exercise-stimulated MetFlex changed in INT or CON, but carbohydrate oxidation during maximal exercise changed differently, favoring INT [INT +2.6 (95% CI: −6.1, 0.8), CON −1.4 (−2.1, 4.9) mg/kg/min; group * time p = 0.03]. In secondary analyses, those who successfully reduced sedentary time by at least 30 min/day (n = 34) improved insulin-stimulated MetFlex and low-intensity exercise fat oxidation compared to the continuously sedentary (n = 30) [ΔRER +0.03 (−0.01, 0.07) vs. −0.02 (−0.06, 0.03); and FATox +0.2 (−0.3, 0.7) vs. −0.4 (−1.0, 1.0) mg/kg/min, group * time p < 0.05]. Changes in insulin-stimulated MetFlex correlated with changes in standing and insulin sensitivity. Thus, successfully reducing daily sitting by at least half an hour can improve MetFlex, with parallel insulin sensitivity enhancements, and aid in cardiometabolic disease prevention in risk populations.